(untitled) (Journal of Management and Educational Sciences, 2025)
This study examines the causes of workplace accidents occurring in educational institutions, how these accidents are perceived by school stakeholders (teachers, administrators, support staff), and proposed solutions to address them. The research was conducted with a total of 30 education staff members working in primary schools in Samsun, middle schools in Malatya, and vocational high schools in Ankara. Semi-structured interviews with the participants were evaluated through content analysis, and the findings were presented using a theme-category-code structure. According to the results, work accidents in primary schools are mostly caused by student behavior and physical infrastructure deficiencies. In middle schools, student carelessness, narrow classroom spaces, and lack of supervision stand out, while in vocational high schools, accidents are generally more dangerous and severe in nature, related to the use of technical equipment, contact with chemical substances, and the nature of practical education. Significant differences were observed in participants’ perceptions of work accidents; while some teachers considered accidents to be inevitable and normal, others emphasized their preventability. It was determined that occupational health and safety awareness has not been fully established at the institutional level in all school types. The study suggests recommendations for developing a safety culture in educational institutions, increasing systematic safety training for students and staff, addressing physical infrastructure deficiencies, and clarifying the definition of workplace accidents.